Análise da aplicabilidade dos Objetivos de Desenvolvimento Sustentável na associação de catadores de materiais recicláveis Associar Recicle Mais Curitiba, Paraná - Perez Júnior, Fernando Richard Lima (2023)
The Sustainable Development Goals (SDGs) were established in 2015 by the UN with the purpose of implementing an action plan that would strengthen universal peace and the eradication of poverty in the world. There are 17 objectives and 169 goals that make up the 2030 Agenda, covering areas that involve people, the planet, prosperity, peace and partnerships. Brazil is a signatory to this Agenda and all sectors of society can contribute to implementing its objectives. The municipality of Curitiba, through Law nº 15.538/2019, established criteria for sustainable development and enabled the offer, by all sectors, of proposals and solutions. In this context, there are associations and cooperatives of recyclable materials in the municipality, which, due to their sorting operations, can contribute, within their production chain, to the implementation of the SDGs. The main objective of this research was to verify the applicability and fulfillment of the SDGs by the association of recyclable material collectors Associar Recicle Mais, active in the city of Curitiba, with a view to meeting the goals proposed by the UN in the 2030 Agenda and in accordance with the sustainable development law of Curitiba. The investigation method included the collection and analysis of the institutional records of the association of collectors Associar Recicle Mais, informal conversations with the associates and the observation of the productive activities, during six on-site visits, between December 2021 and March 2022. Applicability of the SDGs analyzed the association's production chain as well as its management, with observation of the points of greatest impact for classifying the goals. The results of the diagnosis show that SDG 1 - eradication of poverty, SDG 5 - gender equality, SDG 8 - decent work and economic growth, SDG 10 - reduction of inequalities, SDG 11 sustainable cities and communities, SDG 12 sustainable consumption and production and SDG 17 – partnerships and means of implementation, were the objectives met by Associar Recicle Mais. Regarding SDG 1, it was found that the per capita income of the collectors keeps them outside the extreme poverty line. Gender equality, goal of SDG 5, was observed with the participation of women in leadership and administrative management of the association As for SDG 8, it was verified that the association promotes dignified working conditions, following labor and safety laws. SDG 10, on the other hand, is contemplated with the promotion of fair incomes and social inclusion and defense. SDG 11 was analyzed with proof of results regarding the rate of waste that impacts materials destined for landfills and dumps. Prevention, reduction, recycling and reuse of waste in the city of Curitiba, through environmental education actions and distribution of information materials, contribute to SDG 12. And, finally, SDG 17, which collaborates for the partnership between the association of collectors through the interface with public policies, especially in the municipality of Curitiba with the Ecocidadão program. It is concluded that the work carried out by the association Associar Recicle Mais fulfills its role in meeting the 2030 Agenda for seven of the sustainable development goals. Furthermore, it was verified that the association serves as an instrument for the development and reach of sustainable development in the city of Curitiba.